Retraction notice; Some Problems Connected with Diametrically Contractive Maps and Fixed Point Theory With Python Programming Language: S. M. Khairnar, M. More - Team, Support (Thai Journal of Mathematics, 2009)
The author has plagiarized part of a paper that had already appeared in the [M. Baronti, E. Casini, and P.L. Papini, Diametrically contractive maps and xed point. Fixed Point Theory and Applications Volume 2006, Article ID 79075, Pages 18. DOI 10.1155/FPTA/2006/79075] One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. The scientic community takes a very strong view on this matter and we apologize to readers of the journal that this was not detected during the submission process.